Dari Limbah Menjadi Berkah: Strategi Karang Taruna Mengelola Sampah Sayur untuk Pupuk Organik Berkelanjutan - Refranisa, Refranisa; Nugroho, Lucky; Mudita, Mudita; Najuah, Najuah; Purnama, Adhy; Mihadi Putra, Yananto; Nurlinayanti, Leni (Lembaga Layanan Pendidikan Tinggi Wilayah III DKI Jakarta, 2025)
The problem of vegetable waste management in Ciputri Village, especially in RT 05, has caused various negative impacts on the environment and public health, such as clogged waterways, local flooding, foul odors, and increased fly populations. In fact, organic waste has the potential to be processed into liquid organic fertilizers and ecoenzymes that benefit agriculture and the environment. This Community Service activity empowers Karang Taruna as a driving force in managing vegetable waste into value-added products. The approach includes technical training in manufacturing organic fertilizers based on anaerobic fermentation, continuous mentoring, and preparing practical guidelines to ensure the program's sustainability. The results of the activities showed a significant increase in the knowledge and skills of Karang Taruna members, the achievement of organic fertilizer production exceeding the initial target, and the start of implementing a household-based waste management system. The main recommendation of this activity is the need to strengthen cooperation networks, continuous mentoring, and the development of marketing strategies for processed products to maintain sustainability and expand the program's benefits.